2016
DOI: 10.6061/clinics/2016(02)02
|View full text |Cite
|
Sign up to set email alerts
|

The influence of (central) auditory processing disorder on the severity of speech-sound disorders in children

Abstract: OBJECTIVE:To identify a cutoff value based on the Percentage of Consonants Correct-Revised index that could indicate the likelihood of a child with a speech-sound disorder also having a (central) auditory processing disorder.METHODS:Language, audiological and (central) auditory processing evaluations were administered. The participants were 27 subjects with speech-sound disorders aged 7 to 10 years and 11 months who were divided into two different groups according to their (central) auditory processing evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
0
17
0
6
Order By: Relevance
“…Muluk, et al [ 14 ] found poorer gap detection performance in children with previous language delay and SSD. Similarly, Vilela, et al [ 15 ] reported reduced auditory processing performance in children with SSD. Moreover, children with SSD performed poorly in auditory and visual sustained-attention tasks, as well as in gap detection and frequency pattern tasks [ 16 ].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Muluk, et al [ 14 ] found poorer gap detection performance in children with previous language delay and SSD. Similarly, Vilela, et al [ 15 ] reported reduced auditory processing performance in children with SSD. Moreover, children with SSD performed poorly in auditory and visual sustained-attention tasks, as well as in gap detection and frequency pattern tasks [ 16 ].…”
Section: Introductionmentioning
confidence: 91%
“…As stimuli, 0 to 3 silenced gaps are embedded within 6-second white noise. There are ten different gap durations (2,3,4,5,6,8,10,12,15, and 20 ms), and the duration or location of the gaps within the noise is pseudorandomized. As each gap appears six times in each track, a total of 60 gaps were presented.…”
Section: Test Of Auditory Temporal Resolution (Gaps-in-noise Test)mentioning
confidence: 99%
“…Speech perception is an important stage in the development of speech sounds in children [15,25,51,52], and its role is described as a mediator for learning sound production. With this in mind and because of the difficulties observed in children with SSD, several studies have been conducted to investigate the central auditory processing (CAP) [18,53] and electrophysiological responses obtained through auditory-evoked potentials in Brazilian-Portuguese speaking children with SSD. These studies seek to identify the auditory-perceptual characteristics of children with this speech disorder as well as the evidence of altered auditory processing and the lack of maturity-integrity of auditory pathways that could compromise auditory feedback, which is extremely important for phonological development.…”
Section: Relationship Between Auditory and Cognitive-linguistic Procementioning
confidence: 99%
“…Another recent study [53] was conducted to identify a cutoff value based on the PCC-R [58] metric that could indicate the likelihood of a child with SSD also having a CAPD. Language, audiological, and CAP evaluations were administered.…”
Section: Advances In Speech-language Pathologymentioning
confidence: 99%
“…Além do reconhecimento da LIBRAS como língua oficial os surdos obtiveram por meio do decreto 5.626/2005 o acesso à interpretes de LIBRAS em locais públicos como: escolas, igrejas, faculdades, e principalmente em ambientes hospitalares e de atendimento à saúde, entretanto como qualquer outro grupo de minoria da nossa sociedade os surdos não conseguem ter os seus direitos respeitados integralmente principalmente em questões que envolvam à saúde(NEVES et al,2016).Estas dificuldades que os surdos enfrentam foram comprovadas no estudo efetuado por Nóbrega et al (2012), onde os resultados desta pesquisa descreveram que as principais reclamações dos surdos estão relacionadas aos serviços prestados na área da saúde, sendo que a maior reclamação a comunicação ineficaz e ineficiente…”
unclassified